Education on rheumatology in Poland. Part I – Teaching of medical students - Zimmermann-Górska, Irena (Reumatologia/Rheumatology, 2005)
The need of prioritisation of rheumatic diseases in undergraduate education as well as EULAR programme for medical students are presented. Moreover, an actual status of teaching methods in the Polish universities is discussed.